Preconception Health Education is Provided to Healthy Childbearing Couples in The Preconception Phase - Irma Linda; Elisabeth Surbakti; Rismahara Lubis; Cecep Triwibowo (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Several biological, behavioral, and social preventative strategies can improve the chances of having a healthy baby during pregnancy. Preconception health care spans the entire reproductive life cycle. Early preconception counseling should attempt to improve both women's and men's sexual and reproductive health. It should begin with early instruction on healthy lifestyle behaviors, safe sex, and pregnancy planning for childbearing couples. This research aims to develop preconception health education for family-based childbearing age couples planning a healthy pregnancy in Deli Serdang district. The Equivalent Time Series Samples approach was employed in this study as a quasi-experimental approach. The total sample size was 90 couples of reproductive age. The analysis in this study was carried out descriptively to see the characteristics of each variable studied and to measure the effect of providing health education during the preconception period on the knowledge and perception of Couples of Childbearing Age about preconception health using a paired sample T test. The intervention provided is health education about preconception health provided to couples of childbearing age. The implementation of the research has received approval from the Health Research Ethics Committee of the Medan Health Polytechnic with the number: 01.25.174 /KEPK/POLTEKKES KEMENKES MEDAN 2023. There is a difference in the average variable knowledge of couples of childbearing age at pretest and posttest with an increase of 5, 2778, and there is also an increase in the perception variable with an increase of 0.8889, and the results of statistical tests using the Paired Samples Test obtained show differences in respondents' knowledge and perceptions before and after the intervention. Family-based preconception health education has been effective in raising the awareness and attitudes of childbearing couples regarding the planning and preparation of a healthy pregnancy as well as in motivating them to seek a check-up at a health care facility. Keywords: Health Behavior, Health Services, Preconception Care, Pregnancy